Triple positive solutions for m-point boundary-value problems of dynamic equations on time scales with p-Laplacian - Abdulkadir Dogan (Electronic Journal of Differential Equations, 2015)
In this article we study the existence of positive solutions for m-point dynamic equation on time scales with p-Laplacian. We prove that the boundary-value problem has at least three positive solutions by applying the five functionals fixed-point theorem. An example demonstrates the main results.